Avaliação da lixiviação de agrotóxicos em diferentes tipos de solos - Müller, Jônatas (2022)
With the constant growth of the world population, the need for food production increases. Aiming to enhance harvests, the use of agrochemicals in planting only increases. With this uncontrolled use, there are growing concerns about the contamination of soil and water with the possibility of leaching of these chemicals. In view of this scenario, this work had as one of its objectives, the survey and comparison of software that simulate the probability of leaching of pesticides. The functionalities of the following softwares were described: ARAQUÁ, HIDROSOLO, ACHA, AGROSCRE, EXPRESS and GeoPEARL, listing their input variables, their functionalities and the ways of delivering their results. Next, seven criteria were created for comparison between the programs, with different weights for determining the choice of software for the analyses. After these comparisons were made, it was concluded that the software with the best performance was ARAquá, due to its friendly interface, easy to obtain parameters, and fully editable database. The other objectives of this work were to carry out simulations to show possible leaching of pesticides into the groundwater. A total of 32 simulations were performed, with the herbicides glyphosate and 2,4-D. In the simulated scenarios, a Distrofic Red Latosol soil from Passo Fundo/RS and a Yellow Red Argissolo from Cáceres/MT were used, as well as application doses of these pesticides as recommended by the manufacturers and twice these values. The values for precipitation and evapotranspiration were adapted according to the climate of each location. Finally, it was concluded that glyphosate herbicide does not leach, mainly due to the high value of its sorption coefficient. Meanwhile, 2,4-D showed leaching, especially in Passo Fundo/RS due to the higher volume of precipitation, but in extremely low concentrations, presenting no environmental risk.